TANGGUNG JAWAB PIDANA BAGI PEJABAT PEMBUAT AKTA TANAH DALAM TRANSAKSI ATAS DOKUMEN PALSU - Maharani, Nadya Satwika; Darmadi, A.A. Ngurah Oka Yudistira (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 06 (2024), 2025)
The purpose of this writing is to find out about legal guidelines for carrying out criminal liability that can be imposed on authorities who make land deeds for providing false documents for transactions and obtaining land deeds from sale and purchase transactions. The exploration strategy utilized in this composing is standardizing legitimate examination involving a legal methodology and a procedure for looking through lawful materials, in particular the library technique.The result of this writing is the criminal burden imposed on the authorities who make land deeds or notaries from incidents of falsifying land sale and purchase deed documents using Articles 263 and 264 of the Criminal Code and the need for more specific legal protection as a form of criminal responsibility in order to reduce arbitrary actions arbitrarily without any strong reason.